2013
DOI: 10.1093/qje/qjt012
|View full text |Cite
|
Sign up to set email alerts
|

The Missing Wealth of Nations: Are Europe and the U.S. net Debtors or net Creditors?*

Abstract: This paper shows that official statistics substantially underestimate the net foreign asset positions of rich countries because they fail to capture most of the assets held by households in offshore tax havens. Drawing on a unique Swiss dataset and exploiting systematic anomalies in countries' portfolio investment positions, I find that around 8% of the global financial wealth of households is held in tax havens, three-quarters of which goes unrecorded. On the basis of plausible assumptions, accounting for unr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
284
2
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 392 publications
(299 citation statements)
references
References 40 publications
5
284
2
8
Order By: Relevance
“…But if it entrusts assets to a Swiss bank, there is no automatic reporting: French authorities have to rely on self-reporting and tax evasion is possible. 4 Using official Swiss statistics and anomalies in the international investment data of countries, Zucman (2013) estimates that around 8 percent of households' global financial wealth is held in tax havens. This figure implies substantial tax revenue losses due to outright fraud.…”
Section: A Policies To Prevent Offshore Tax Evasionmentioning
confidence: 99%
“…But if it entrusts assets to a Swiss bank, there is no automatic reporting: French authorities have to rely on self-reporting and tax evasion is possible. 4 Using official Swiss statistics and anomalies in the international investment data of countries, Zucman (2013) estimates that around 8 percent of households' global financial wealth is held in tax havens. This figure implies substantial tax revenue losses due to outright fraud.…”
Section: A Policies To Prevent Offshore Tax Evasionmentioning
confidence: 99%
“…For our purposes, the issue is whether the existence of wealth offshore tends to distort our measure of gross (of tax) returns on wealth. If wealth is held abroad mostly to profit from more rewarding investment opportunities not available at home (as argued by Zucman, 2013), then ours are conservative estimates of the heterogeneity in returns and their correlation with wealth. If we drop people in the top 0.5% or 1% of the wealth distributionwhere all wealth offshore seems to be sitting according to Alstadsaeter et al (2017) -our results are unaffected.…”
Section: Some Conceptual Remarksmentioning
confidence: 93%
“…The International Monetary Fund (IMF) (2013a) argues that more progressive taxation on higher income groups is needed to mitigate widening income gaps, but in the era of globalization, the imposition of higher tax rates on wealth and capital can provoke tax evasion and avoidance. Zucman (2013) showed that almost 8% of the global financial wealth of households was in the custody of tax haven countries. The OECD (2012a) reported that the size of the tax revenue to GDP ratio does not always result in the same redistributive impact.…”
Section: Redistributive and Progressive Effects Of Income Taxesmentioning
confidence: 99%